SOSIALISASI MANFAAT AIR REBUSAN DAUN KELOR (MORINGA OLEIFERA) DALAM MENURUNKAN KADAR ASAM URAT (GOUT ARTHRITIS) PADA ANGGOTA KELUARGA DI UPTD PUSKESMAS SUKATANI PURWAKARTA - Herwed Nelson; Grace Evelyn; Nur Septian (Bajang Institute, 2025)
High uric acid (gout arthritis) is a metabolic disorder caused by increased uric acid levels in the blood, which causes joint pain and inflammation. One complementary therapy that can be used is consuming boiled water from Moringa oleifera leaves, which contain active compounds such as flavonoids, saponins, and tannins that play a role in lowering uric acid levels. This community service activity aims to improve the knowledge and skills of the community in the work area of ​​the Sukatani Community Health Center UPTD, Purwakarta Regency, in administering boiled water from Moringa leaves to lower uric acid levels. The activity implementation method uses a lecture, demonstration, and simulation approach. The activity participated in 40 people consisting of the general public and health cadres. Evaluation was carried out using pre-tests and post-tests to assess knowledge gains, as well as observation of skills during the simulation practice. The results of the activity showed an increase in participants' knowledge from an average of 58% (pre-test) to 89% (post-test). In addition, 90% of participants were able to simulate chest compressions and artificial ventilation with the correct technique. Participants also showed high enthusiasm in participating in the entire series of activities. Socialization and training on the use of boiled moringa leaves have proven effective in increasing the knowledge and skills of the community in the Sukatani Community Health Center (Puskesmas) work area. Boiled moringa leaves effectively reduced uric acid levels in respondents with mild to moderate gouty arthritis. This therapy can be used as a non-pharmacological, complementary alternative to help control uric acid levels naturally